2005
DOI: 10.1248/cpb.53.684
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Methyl 1-O-(4-Hydroxymethamphetaminyl)-.ALPHA.-D-glucopyranouronate

Abstract: For the purpose of the direct characterization of the intact conjugated form in the urine of a methamphetamine (MA) abuser, 4-hydroxymethamphetamine (4-OHMA) glucuronate, corresponding to one of the metabolites of MA, was synthesized from the commercially available methyl 4-hydroxyphenylacetate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…Synthesis of 5 from 3 through 4 (Scheme 2) was based on a reported procedure [3]. Acylation of 4 was completed within 14 h at rt, and 5 was precipitated by using brine/water in 76% yield as a mixture of anomers (35/65, α/β).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Synthesis of 5 from 3 through 4 (Scheme 2) was based on a reported procedure [3]. Acylation of 4 was completed within 14 h at rt, and 5 was precipitated by using brine/water in 76% yield as a mixture of anomers (35/65, α/β).…”
Section: Resultsmentioning
confidence: 99%
“…Stereoselective β-O-glycosylation of morphine that contains secondary alcohol and tertiary amine has also been reported under Koenigs-Knorr conditions [8]. Stereoselective β-O-glycosylation of a phenol containing a tertiary amine with α-O-trichloroacetimidate glycosyl donor has also been reported [3]. However, stereoselective β-O-glycosylation of a substrate that contains a tertiary alcohol and a secondary amine has not been reported in literature to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…9) Pholedrine, p-hydroxymethamphetamine (p-OHMA) and methamphetamine (MA) hydrochloride were obtained from Sigma (St. Louis, MO, U.S.A.) and Dainippon Pharmaceutical (Osaka, Japan), respectively (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…10, 12, 15 Brown et al 15 used a tri-Oisobutyryl protected trichloroacetimidate as glucuronidating agent. However, we found that use of the tri-O-acetyltrichloroacetimidate 3 16 provided the most practical route to useful Methyl (4-acetamidophenyl-2,3,4-tri-O-acetyl-β-D-glucopyranosid)uronate 4 was obtained using the glucuronide donor 3, paracetamol and BF 3 .OEt 2 in dichloromethane. Base hydrolysis of 4 was achieved using 2 equivalents of K 2 CO 3 in 5:5:1 MeOH:THF:H 2 O.…”
mentioning
confidence: 99%